Sweet potato is a strategic root crop in Oceania: A synthesis of the past research and future direction - Michael, Patrick S.; Peter, Topas M. (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2023)
Sweet potato is an important food, industrial, and pharmaceutical crop worldwide and highly adapted to adverse ranges of agroclimatic conditions, making it one of the strategic crops under climate change. Despite the importance, sustainable crop production continues to be an issue because of the pressure put on land, the decline in soil fertility, the buildup of pests and diseases, and no standardized production practices. Production is highly mechanized in temperate regions, whereas, in the tropics, it is still a subsistence crop confined to subsistence farming systems. These issues are compounded by a lack of generically and agronomically improved genotypes adapted to wider agroecological zones with adaptive tolerance to existing and new stresses. In the recent past, significant progress has been made worldwide; however, the outcomes tend to be locality-specific, and cannot be extrapolated, needing decentralization of the current approaches. This review points out that the crop is a critical strategic crop in the Oceania region because of its ability to grow under adverse ranges of agroclimatic conditions and can produce a reasonable yield. The paper continues to emphasize the current trends in emerging modern technology that can be used to efficiently improve and enhance traits of agronomic importance and wider adaptivity. In addition, land use plans, farming systems, and cultural production practices need to be changed for sustainable production. The need for these is further strengthened by pointing out alternative strategies, e.g., using organic matter as a relatively cheap and readily available source of soil nutrients compared to inorganic fertilizers.